‘Violence can mean a lot of things can't it?’ An exploration of responses to harm associated with indoor sex work in Scotland - Smith, Emma Jane (2015)
The association of violence with sex work has been widely documented within research and policy. This thesis provides a critique and development of such perspectives. Framed from a qualitative approach, it extends current research which has offered limited insight into the realities of how violence is experienced and responded to by sex workers and agencies involved in the provision of support to sex workers. In this way, the research develops beyond a presumption and narrow understanding of violence/harm in sex work to consider how sex workers and service providers experience, define, and thus construct their responses to harm. Findings from the data indicate variation amongst participants in their responses to harm associated with sex work, with experiences of violence or supporting violence and relationships and interactions between sex workers and service providers being important factors in how these responses are constructed. Both sex workers and service providers, however, recognised and understood associations of sex work with violence and victimisation, and related attempts to encourage individuals to cease or limit involvement in sex work, although this may not apply or be appropriate to all experiences of sex work and sex workers. The thesis contends that in order to gain an informed understanding of, and develop responses to, harm associated with sex work, it is important to consider the diversity of existing experiences of sex work. This should include alternative understandings and experiences of harm that are not limited to, or focused on, violence within sex work, as informed by the experiences of different sex workers. In doing so, there is the potential to better understand and accommodate a range of sex workers’ experiences, needs and interests in ways that do not impact on sex workers’ safety, or contribute to continued stigmatisation or exclusion, where some sex workers do not identify with a view of their work as harmful, or wish to exit sex work. Consequently this could aid the provision and development of services that respect and offer support where required, for different experiences of sex work amongst sex workers